Posttransplant Lymphoproliferative Disease Presenting as an Extracranial Mass - Reuben J. Arasaratnam; Alejandro Restrepo (Case Reports in Transplantation)
Posttransplant lymphoproliferative disease is a serious complication following stem cell and solid organ transplantation. Early recognition of the disease is important in facilitating timely therapy and improving long-term outcomes. We report a renal transplant recipient presenting with an extracranial frontoparietal soft tissue mass that was subsequently diagnosed as a B-cell lymphoma. The patient was treated successfully with immunosuppression reduction, anti-CD20 monoclonal antibody therapy, and cytotoxic chemotherapy. Our case highlights the importance of recognizing soft tissue masses in the head and neck as a potential clinical manifestation of PTLD in solid organ transplant recipients.